Effect of frequency and pattern of night shift on hypertension risk in female nurses: a cross-sectional study. Issue 6 (June 2021) - Zhao, Bin; Li, Jing; Feng, Di; Liu, Jie; Hao, Yuming; Zhen, Yanjie; Hao, Xiaoran; Liu, Fude; Zuo, Aifang; Yang, Xiulan; Chen, Ximin; Jia, Rufu; et al.
Abstract : Objectives: Understanding the effect of night shift on hypertension risk in nurses is important to improve the health of nurses and ensure patient safety. This study aimed to evaluate the effect of the frequency and pattern of night shift on hypertension risk and the interaction of them in female nurses. Methods: This cross-sectional study constituted 84 697 female nurses in 13 cities in China. The main contents of the survey included SBP, DBP, the frequency and pattern of night shift, and some other factors that might be associated with hypertension. Logistic regression analyses were used to calculate ORs and 95% CIs to estimate the effect of the frequency and pattern of night shift on hypertension risk and the interaction of them in relation to hypertension risk. Results: Having more than 5 to 10 or more than 10 night shifts per month were significantly more likely to be hypertensive (OR 1.19, 95% CI 1.10–1.28; OR 1.32, 95% CI 1.13–1.54), whereas having less than or equal to 5 night shifts per month was not (OR 1.05, 95% CI 0.95–1.16). The patterns of night shift were all associated with a higher probability of hypertension and participants engaging in rapidly rotating night shift had a lower OR (1.14) than those having slowly rotating night shift (1.23) and permanent night shift (1.46). No significant interaction was observed between the frequency and the pattern of night shift ( P interaction  = 0.281). Conclusion: The frequency and pattern of night shift were associated with hypertension risk in female nurses and no significant interaction was observed between them.